The Effect of Product and Service Diversification in Ecotourism Business Management on Beaches in Bali - Ramdhan Kurniawan; Siska Jeanete Saununu; Iwan Harsono; Henny Budhysetia Dewi (West Science Interdisciplinary Studies, 2024)
This research investigates the dynamic interplay between ecotourism, product and service diversification, and their impact on the beaches of Bali. Through a quantitative analysis involving 150 tourists and 150 local businesses, the study explores awareness levels, preferences, and economic outcomes associated with ecotourism practices. Descriptive statistics reveal a heightened awareness among tourists and a prevalent adoption of diversification strategies by local businesses. Correlation analysis establishes strong connections between tourist awareness, preferences for diversified destinations, and the positive correlation between business diversification and community involvement. Regression analysis underscores the economic advantages linked to businesses implementing diversification strategies. Comparative analyses shed light on subgroup differences, emphasizing the influence of awareness and diversification on preferences and economic impact. The discussion underscores the implications for sustainable ecotourism, emphasizing the role of collaboration among businesses, communities, and policymakers. The study contributes valuable insights to the discourse on sustainable tourism practices, offering actionable recommendations for the ecotourism industry on Bali's beaches.